2001
DOI: 10.1074/jbc.m100496200
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Isozyme of 2′-5′ Oligoadenylate Synthetase Is a Dual Function Proapoptotic Protein of the Bcl-2 Family

Abstract: 2-5(A) synthetases are a family of interferon-induced enzymes that polymerize ATP into 2-5 linked oligoadenylates that activate RNase L and cause mRNA degradation. Because they all can synthesize 2-5(A), the reason for the existence of so many synthetase isozymes is unclear. Here we report that the 9-2 isozyme of 2-5(A) synthetase has an additional activity: it promotes apoptosis in mammalian cells. The proapoptotic activity of 9-2 was isozyme-specific and enzyme activity-independent. The 9-2-expressing cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
53
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 26 publications
2
53
0
Order By: Relevance
“…Importantly, we have found that Notch activation in keratinocytes causes selective suppression of some interferon-responsive genes, while inducing others (Supplementary Table 2), pointing to the existence of a novel mechanism for the fine tuning of the interferon response, which may be of particular significance for modulation of growth-differentiation control as opposed to the antiviral function. Several of the interferon-responsive genes under negative Notch control in keratinocytes have been previously implicated in positive growth control, apoptosis, and/or tumorigenesis (e.g., see Ghosh et al 2001;Carpten et al 2002;Wasylyk et al 2002;Zhang and Pagano 2002), with an impact that is likely to extend to keratinocytes. We note in particular the down-modulation of Sp100, a key component of nuclear bodies involved in chromatin control (Moller et al 2003), which parallels the opposite up-regulation of PML, another nuclear body component, in cells with loss of p63 expression (Bernassola et al 2005;Keyes et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we have found that Notch activation in keratinocytes causes selective suppression of some interferon-responsive genes, while inducing others (Supplementary Table 2), pointing to the existence of a novel mechanism for the fine tuning of the interferon response, which may be of particular significance for modulation of growth-differentiation control as opposed to the antiviral function. Several of the interferon-responsive genes under negative Notch control in keratinocytes have been previously implicated in positive growth control, apoptosis, and/or tumorigenesis (e.g., see Ghosh et al 2001;Carpten et al 2002;Wasylyk et al 2002;Zhang and Pagano 2002), with an impact that is likely to extend to keratinocytes. We note in particular the down-modulation of Sp100, a key component of nuclear bodies involved in chromatin control (Moller et al 2003), which parallels the opposite up-regulation of PML, another nuclear body component, in cells with loss of p63 expression (Bernassola et al 2005;Keyes et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The first molecular clone for an OAS was obtained by Michel Revel's lab [10]. Biochemical characterization of OAS proteins by Ara Hovanessian's lab [11][12][13][14] and Ganes Sen's lab [15][16][17][18][19] and a crystal structure by Rune Hartmann and Vivien Yee (in collaboration with Ganes Sen and Just Justesen) [20] have led to functional and structural insight into the OAS family of Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript.…”
mentioning
confidence: 99%
“…Both apoptosis and the antiviral effects of IFN against encephalomyocarditis virus are defective in RNase L Ϫ/Ϫ MEF cells and mutant mice devoid of RNase L (5). However, the 9-2 isoform of OAS1 shows comparable apoptotic activity in RNase L Ϫ/Ϫ cells as wild-type fibroblasts (15). It will be interesting to learn whether the presence or absence of RNase L affects the flavivirus resistance͞ susceptibility phenotype.…”
mentioning
confidence: 99%
“…That is, does the wild-type 1b͞L1 OAS protein in resistant mice have a dsRNA-independent function? Pertinent to this possibility, the 9-2 isoform of mouse OAS1 recently has been shown to be a dual-function protein that independently can synthesize 2-5A oligomers and promote cellular apoptosis (15). The proapoptotic activity, which is OAS-isoform specific, depends upon a functional Bcl-2 homology 3 domain present in the C-terminal region that interacts with the Bcl-2 and BclxL antiapoptotic proteins (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation